The Effect of Giving A Compress of Sirih Leaves Boiled Water on The Level of Scabies - Eva Dwi Ramayanti; Satria Eurika Nurseskasatmata (Universitas STRADA Indonesia, 2020)
Scabies is a type of skin disease that often attacks santriwati. The purpose of this study is to know the influence of compression of betel leaf boiled water to level scabies.This research is Pre Experimental. The population in this study are all santriwati who experience tingkat scabies. Sample 18 respondents based on Simple Random Sampling. The test used is Wilcoxon. Based on Wilcoxon test, p-value is 0.000, because p-value <α (0.05) then H0 is rejected and H1 is accepted which means there is influence of compression of boiled water of betel leaves to level scabies santriwati, it is found that the test result is Negative rank Meaning between before and after given Compost Water Supply boiled betel leaves there is a decrease in level scabies santriwati. Is expected to increase the knowledge of responden in preventing and lowering scabies an can improve the quality of health